Strategi Promosi Pemasaran Ikan Koi Di CV. Agra Koi Farm Blitar - Ardhi Hendra Westya; Moch. Saleh Udin; Rafikhein Novia Ayuanti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
The main problem in this research is how to implement the marketing promotion strategy for koi fish by CV. Agra Koi Farm Blitar uses SWOT Analysis, aiming to find out and describe the right promotional strategy using SWOT Analysis. This can be seen from the lack of activity or promotional activities carried out by CV. Agra Koi Farm Blitar and many competitors in the same business field. The type of research used is qualitative research. The data collection techniques used were observation, documentation, interviews and literature study. The instruments in this research are the researcher himself, interview guidelines, documentation and field notes. The analysis technique used is SWOT Analysis using the SWOT Matrix. Based on the results of the IFAS and EFAS matrix analysis, it is proven that the strength value is greater than the weakness value, namely with a difference of (+) 0.56. Meanwhile, the opportunities value is greater than the threats value, namely with a difference of (+) 0.77. The SWOT diagram shows that the shaded area is in quadrant I. The strategy that must be implemented in this condition is to support aggressive growth policies (Grow Oriented Strategy). Under these conditions, the most appropriate strategy was implemented by CV. Agra Koi Farm Blitar uses the SO strategy, namely a strategy that utilizes strengths to manage existing opportunities.